El establecimiento de la agricultura en Magallanes (1843-1880) - Martinic Beros, Mateo (Historia, 2000)
Since Chilean republic established its actual jurisdiction in the strait's Magallanes region, in 1843, their rulers consider the introduction of agriculture as a necessary assumption for the development of the colonization and peopling of the southern territory. This paper gives an account of the successive trials done to introduce and cultivate vegetables and forage, and about their precarious results in the former Fuerte Bulnes during the first five years" Later on, with the change of the colonial settlement to Punta Arenas, the better conditions of soils and climate allow the strengthening and enlargement of the agricultural crops. In that way, through 1880 the activity could be considered as a interesting branch of the emerging magellanic economy, nevertheless with limited development possibilities at that moment.